2014
DOI: 10.1021/es403950y
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-Specific Biodegradation of Nonylphenol in River Sediments and Structure-Biodegradability Relationship

Abstract: Nonylphenol (NP), a well-known environmental estrogen with numerous isomers, is frequently found in surface water and sediments. Recent studies showed that NP isomers exhibited different estrogenicity. However, at present little information is available on its isomer-specific degradation in the bed sediment, which is the primary sink of NP in surface aquatic systems. In this study, we investigated the biodegradability of 19 NP isomers in two river sediments under oxic and anoxic conditions. Under oxic conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 33 publications
3
16
0
2
Order By: Relevance
“…Hao et al (2009) considered the biodegradation of a few NP isomers in a sequencing batch reactor and observed that biodegradability followed a trend of NP 36 (75.4%) > NP 111 (42.9%) > NP 170 (40.7%) > NP 194 (36.2%), which was in agreement with that observed in the current study. In an oxic river sediment, alkyl chain length and a-substituent types were also found to greatly influence the biodegradation of NP isomers (Lu and Gan, 2014). However, in river sediments, the effect of a-substituent types appeared to be less monotonous than that in the bioreactor, while an opposite effect was observed for the alkyl chain length.…”
Section: Isomer Structureebiodegradation Relationshipsmentioning
confidence: 89%
See 3 more Smart Citations
“…Hao et al (2009) considered the biodegradation of a few NP isomers in a sequencing batch reactor and observed that biodegradability followed a trend of NP 36 (75.4%) > NP 111 (42.9%) > NP 170 (40.7%) > NP 194 (36.2%), which was in agreement with that observed in the current study. In an oxic river sediment, alkyl chain length and a-substituent types were also found to greatly influence the biodegradation of NP isomers (Lu and Gan, 2014). However, in river sediments, the effect of a-substituent types appeared to be less monotonous than that in the bioreactor, while an opposite effect was observed for the alkyl chain length.…”
Section: Isomer Structureebiodegradation Relationshipsmentioning
confidence: 89%
“…The extraction was repeated for two consecutive times. The cleanup procedure was similar to that in a previous study (Lu and Gan, 2014). Briefly, the extract was concentrated to about 1 mL and passed through a HyperSep Florisil SPE column (Thermo Scientific, Pittsburgh, PA) with a 5-g sorbent bed.…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Another source of their presence in the environment involves the breakdown of ethoxylates (octylphenol ethoxylates; OPEs, and noylphenol ethoxylates; NPEs) as well as leaching from plastic debris [153]. OPs and NPs persist in the environment and are particularly toxic with their endocrine disrupting activities [50,106,148].…”
Section: Octylphenols (Ops) and Nonylphenols (Nps)mentioning
confidence: 99%